2017
DOI: 10.1083/jcb.201701045
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of dynamic microtubules by mDia1 drives Tau-dependent Aβ1–42 synaptotoxicity

Abstract: Qu et al. present the first evidence that mDia1-mediated stabilization of dynamic microtubules (MTs) and induction of tubulin posttranslational modifications drive tau hyperphosphorylation and synaptotoxicity, providing a novel target for therapy and the first mechanistic explanation as to why a dynamic MT cytoskeleton must be maintained to prevent neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 108 publications
6
68
1
Order By: Relevance
“…We have identified that Aβ42o-mediated AMPK over-activation also signal through phosphorylation of Tau on S262 in parallel to MFF-ULK2 phosphorylation/activation and lead to dendritic mitochondrial remodeling and synapse loss. Further work will be required to understand if Aβ42o-induced AMPK-Tau signaling plays a direct role in mitochondrial fission and/or mitophagy machinery or plays an indirect role through its postsynaptic signaling function (Ittner and Gotz, 2011;Ittner et al, 2010) and/or its ability to regulate microtubule dynamics (Qu et al, 2017) thereby indirectly influence mitochondrial remodeling. Lastly, what makes this molecular mechanism attractive for development of new therapeutic approaches is that it is a true bonafide stress-response signaling pathway (Mairet-Coello and Polleux, 2014) i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified that Aβ42o-mediated AMPK over-activation also signal through phosphorylation of Tau on S262 in parallel to MFF-ULK2 phosphorylation/activation and lead to dendritic mitochondrial remodeling and synapse loss. Further work will be required to understand if Aβ42o-induced AMPK-Tau signaling plays a direct role in mitochondrial fission and/or mitophagy machinery or plays an indirect role through its postsynaptic signaling function (Ittner and Gotz, 2011;Ittner et al, 2010) and/or its ability to regulate microtubule dynamics (Qu et al, 2017) thereby indirectly influence mitochondrial remodeling. Lastly, what makes this molecular mechanism attractive for development of new therapeutic approaches is that it is a true bonafide stress-response signaling pathway (Mairet-Coello and Polleux, 2014) i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This post translational modification is a hallmark of stability because it increases mechanical resilience to ensure the persistence of long-lived microtubules (Xu et al, 2017b) (Janke and Montagnac, 2017). Its downregulation, resulting from either HDACs inhibition or GSK3β activation, has been correlated to microtubule dynamics alteration in different cell types (Garza et al, 2018) (Bacon et al, 2015) (Qu et al, 2017). In these cells, Dock5 acts as a key signaling adaptor that brings Akt into the vicinity of GSK3β, allowing it to phosphorylate GSK3β on serine 9 and inhibit its activity (Ogawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although lithium chloride treatment increases in fine microtubule acetylation level, the latter is much higher than in control osteoclasts (figure 5E). That might affect the expected rescue because both positive and negative regulation of acetylation impact microtubules growth characteristics (Qu et al, 2017) (Zilberman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sections were cooled down for 15min, rinsed 3 times with PBS 1X, permeabilized with 0.01% Triton X-100 for 10min and blocked with NGS (Thermofisher) 10% in PBS 1h at R.T. Primary antibodies incubations were performed o/n at 4°C in NGS 10% PBS 1X buffer. Alexa Fluor fluorescent dyes-conjugated secondary antibodies were diluted 1:200 in 10% NGS-PBS1X and added for 1h at R.T. For IF studies of isolated DRG neurons, cells were fixed with 4% PFA, followed by membrane permeabilization with 0.1% Triton X-100 and then staining with specific primary and secondary antibodies as described in 28 . Acquisition was performed using spinning disk confocal (Olympus DSU) coupled to a camera controller Hamatsu (C10600 ORCA-R 2 ) or epifluorescence microscopy (Olympus IX81) coupled to a monochrome CCD camera (Sensicam QE; Cooke Corporation) and all images were analyzed by ImageJ software.…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, tubulin and MTs functionally interact with TRPV1 22,23 , and -tubulin acetylation appears to be a critical component of the mammalian mechano-transduction machinery 24 . Importantly, anomalies in MT dynamics and tubulin PTMs can drive axon regeneration failure and neurodegeneration [24][25][26][27][28][29][30][31][32] .…”
mentioning
confidence: 99%